Building resilience to conflict through food security policies and programs: Evidence from four case studies - Breisinger, Clemens; Ecker, Olivier; Maystadt, Jean-François; Trinh Tan, Jean-François; Al-Riffai, Perrihan; Bouzar, Khalida; Sma, Abdelkarim; Abdelgadir, Mohamed (International Food Policy Research Institute, 2014)
Food insecurity at the national and household level not only is a consequence of conflict but can also cause and drive conflicts. This paper makes the case for an even higher priority for food security–related policies and programs in conflict-prone countries.